2012
DOI: 10.1007/s11250-012-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of bovine venereal campylobacteriosis in cattle herds in the Lake Chad basin of Nigeria

Abstract: The prevalence of bovine venereal campylobacteriosis (BVC) was investigated in the Lake Chad basin of Nigeria. Preputial washings and cervico-vaginal mucus samples were obtained from 270 cattle presenting a history of abortion and lowered fertility, kept in traditional and institutional farms. All the samples investigated were cultured using standard bacteriological technique. Campylobacter fetus was isolated from six bulls and four cows. In all cattle sampled, the isolation rates were 2.2% for C. fetus subsp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Previous studies already showed negligible percentages for the involvement of Campylobacter spp. in bovine abortion [34], [57]. More samples should be collected to survey the infections caused by these two bacteria in dairy herds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies already showed negligible percentages for the involvement of Campylobacter spp. in bovine abortion [34], [57]. More samples should be collected to survey the infections caused by these two bacteria in dairy herds.…”
Section: Discussionmentioning
confidence: 99%
“…In Minas Gerais, a prevalence of 25.5 % (40/157) was found using DIF in samples of cervical-vaginal mucus from animals with reproductive problems (Stynen et al 2003). In other regions of the world, such as Nigeria, positivity levels of 3.0 % (3/100) have been reported in microbiological examinations of cervical-vaginal mucus samples from cows of reproductive age (Mshelia et al 2012). The difference between the results of the present study and those of other studies could be associated with different types of experimental designs as well as the transport and diagnostic methods used.…”
Section: Bovine Genital Campylobacteriosismentioning
confidence: 99%
“…Some field studies have been done in Nigeria [4,15-18], reporting animal-level prevalences of 2.9-11% and herd-level prevalences of 20-22%; however, these were done on few herds and in limited locations, and in some cases targeted animals with a history of reproductive failure. The occurrence of BGC is believed to be grossly under-estimated and under-reported in Africa [7,10].…”
Section: Introductionmentioning
confidence: 99%